IMPLIKASI PRINSIP MOST FAVOURED NATION TERHADAP PENGATURAN TARIF IMPOR DI INDONESIA - Pebrianto, Dony Yusra (JOURNAL EQUITABLE, 2017)
The existence of trade liberalization is faced with the fact that the competition of countries in trade especially in this case export and import increasingly felt very rapidly. The existence of international legal instruments that are commonly contained in the General Agreement on Tarriff and Trade (GATT) becomes an important point in the international trade regulatory concept for GATT member countries incorporated in the World Trade Organization (WTO). So the principles are also embedded in the drafting of the concept of national law for States that have ratified GATT. Indonesia, one of the countries that have ratified GATT, is bound by these Principles, one of which is the Most Favored Nation Principle which implies the regulation of import tariff in Indonesia. So protection of local commodities is closed even if limited to maintain the continuity of national production.